THE EFFECT OF PRODUCT QUALITY, PRICE AND DIGITAL MARKETING ON CONSUMER SATISFACTION PT. SURACOJAYA ABADI MOTOR PALOPO - Ridwan, Rasmi; Maszudi, Edi; Basir, Adil (Universitas Islam Lamongan, 2025)
This study aims to determine the effect of product quality, price, and digital marketing on consumer satisfaction at Pt. Suracojaya Abadi Motor Palopo on Jalan. Kelapa, Kel. Dangerakko Village, Wara District. The sample taken was 215 respondents who had made transactions at Pt. Suracojaya Abadi Motor Palopo. The data collection technique used a questionnaire via the Google form. The method used in this study is quantitative with data analysis techniques using SPSS 25. The results of the study showed (1) Product Quality does not have a significant effect on consumer satisfaction, (2) Price has a significant effect on consumer satisfaction, (3) Digital Marketing has a significant effect on consumer satisfaction, (4) Product Quality, Price, and Digital Marketing simultaneously have a positive and significant effect on Consumer Satisfaction.